Pengaruh Penerapan Kurikulum Merdeka Terhadap Hasil Belajar Geografi Siswa Kelas X di SMAN 2 Tilatang Kamang - Adini Adia Fitri; Slamet Rianto; Trina Febriani (Departement of Mathematics Education, 2023)
This study aims to find out and analyze data about the effect of implementing the independent curriculum on student geography learning outcomes. The method used in this research is quantitative method using total sampling technique, there are 103 students as the research sample. This research was conducted at SMA Negeri 2 Tilatang Kamang in class X. From the results of this study it was concluded that there was an effect of implementing the independent curriculum on the learning outcomes of geography students in class X SMA Negeri 2 Tilatang Kamang. The regression equation is class XE.1 Y = 89.65 + 0.336X, which means that for every increase in one variable X, the value of variable Y will increase by 0.336 where the application of the independent curriculum affects learning outcomes by 48% (high); both classes XE.2 Y = 91.20 + 1.019X, which means that for every one increase in the X variable, the value of the Y variable will increase by 1.019 where the implementation of the independent curriculum affects learning outcomes by 54% (high); the three classes XE.3 Y=87.63 + 0.912X, which means that for every one increase in the X variable, the value of the Y variable will increase by 0.912 where the implementation of the independent curriculum affects learning outcomes by 57% (high); and the fourth class XE.4 Y = 88.03 + 0.764X, which means that for every one increase in the X variable, the value of the Y variable will increase by 0.764 where the implementation of the independent curriculum affects learning outcomes by 50% (high).